Effect of apamin on responses to BRL 34915, nicorandil and other relaxants in the guinea-pig taenia caeci - Weir, S W; Weston, A H (British journal of pharmacology, 1986)
BRL 34915 (4-64 X 10(-7) M), isoprenaline (0.5-32 X 10(-8) M) and nicorandil (4-64 X 10(-6) M) produced a slowly-developing relaxation of spontaneous tone of the guinea-pig taenia caeci; with no after-contraction on washout. These inhibitory responses were unaffected by apamin (10(-7) M). Adenosine triphosphate (0.06-2 X 10(-3) M) and noradrenaline (1-16 X 10(-7) M) produced a rapid inhibition of spontaneous tone with a prominent after-contraction, especially on washout. Both the inhibitory effect and the rebound contraction were abolished by apamin (10(-7) M). Exposure to both BRL 34915 (64 X 10(-7) M) and to nicorandil (64 X 10(-6) M) produced an increase in the 86Rb efflux rate coefficient which was unaffected by apamin (10(-7) M). Exposure to isoprenaline (32 X 10(-8) M) had no effect on the 86Rb efflux rate coefficient. Exposure to noradrenaline (16 X 10(-7) M) produced an increase in the 86Rb efflux rate coefficient which was abolished by apamin (10(-7) M). The results confirm that both BRL 34915 and nicorandil are capable of opening potassium channels in smooth muscle but show that the channel is not apamin-sensitive.